Effect of quantum confinement in CdSe/Se multilayer thin films prepared by PVD technique. (15th June 2017) - Anandh Jesuraj, S.; Devadason, Suganthi; Melvin David Kumar, M.
Abstract: Quantum confined nanostructures were prepared by depositing alternate CdSe and Se thin layers. The structural and optical characterizations of the prepared samples were carried out using X-ray diffractometer (XRD), Field emission scanning electron microscope (FE-SEM), UV–visible and photoluminescence spectrophotometers. XRD studies revealed that CdSe nanocrystals are polycrystalline in nature with hexagonal phase. The crystallite size of CdSe nanoparticles was found to be in the range of 8–14 nm. FE-SEM images also confirmed that the embedded nanocrystalline CdSe particles are a few nanometers in dimension having a spherical morphology. The quantum confinement of charge carriers in the multilayer (ML) films is evident from the shifting of absorption edge to lower wavelengths in the UV–visible spectra. An increase in the energy band gap with decreasing thickness of the CdSe sub-layer has been ascribed to quantum confinement effect and the subsequent crystallite size calculated from Brus approximation method is ~3.5 nm. Hence, the results indicate that the quantum confinement effect could be realized in CdSe nanocrystallites by ML stacking structure of CdSe and Se in appropriate thickness ratio.